Higher education instructors’ and students’ attitudes toward distance learning - Arouri, Yousef M.; Alshaboul, Yousef M.; Hamaidi, Diala A.; Alshaboul, Asia Y. (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study aimed at exploring the attitudes of higher education instructors and university students regarding distant learning during the COVID-19 epidemic. It took place at a higher education institution of Jordan. Using a mixed method approach, the researchers developed a two-part questionnaire and a semi-structured interview. The questionnaire was distributed questionnaire to 167 instructors and 349 students from the University of Jordan (UJ). The findings showed that the participants have a moderately favorable attitude toward distant learning. Additionally, the findings revealed no statistically significant differences (α=.05) in the attitudes of UJ instructors and students toward distance learning during the COVID-19 pandemic attributedto the study variables. Furthermore, the interviews revealed several themes that the university instructors and students identified as influencing the general effectiveness of their distance learning experience, including access to online platforms and professional training, offering electronic equipment, and protecting the integrity of exams. The study recommends that higher education institutions reconsider the concept of distance learning, considering lessons acquired from the era of compulsory distance learning.